Feasibility study on producing functional parts using molding technology - Elewe, Adel Muhsin (2014)
The mechanical and electrical conductivity of a system based on ABS (acrylonitrile butadiene styrene) filled with metal powder have been studied. Copper powder having different percentage was used as fillers. Polymer composite investigated to produce high electrical conductivity from a low-cost thermoplastic with low conductive filler loading concern over the process ability. The composite preparation conditions allow the formation of a metal powder distribution in the polymer matrix volume to create a good network of electrically conductive fillers. The main objective of this study is to investigate the feasibility of producing functional composit material based on effective mixture. And also to formulate the metal-plastic which can produced by molding technology. ABS is compounded with a copper powder in the mixing machine at 190 to 230ºC for 15 minutes at 30 rpm, then charged to the plastic grinder machine in order to form the composite in suitable size to feed it in molding machine. The influence of viscosity on processing selection is being mapped by MFI test in order to perform the samples in a proper molding technology. The compositions were adjusted as the polymer volumes were equal to 10%, 20% for injection molding machine process and 30% to 70% were used in hot press molding machine process. In order to understand the variation in electrical and mechanical properties, several tests were performed such as density, porosity, tensile, hardness and IV test. Experimental data shows that the strength of the composite improved while the electrical resistivity decreases with the arising of percolation thresholds. The key parameter in this case is the packing factor F which equal to 0.46, represents the maximum point of percolation threshold that achieve conductive composite.